Numerical simulation of behavior of multi-layered metal targets impacted by high-velocity striker - Orlov, Maxim Yurievich (Proceedings of the Institution of mechanical engineers, Part C: Journal of mechanical engineering science)
In the paper, the results of numerical simulation of perforation of monolithic and multilayered targets are presented. The objects of study were monolithic, two-layer, three-layer and air gap targets made of steel 3. The research was aimed to investigate the influence of an additional layers location into impact resistance upon high-velocity impact (initial velocity was more than the ballistic limit of all targets). The behaviour of materials was described from standpoint of a phenomenological macroscopic model of continuum mechanics. The modified lagrangian method was used for numerical simulation of perforation process. Before numerical research test calculations were performed. Good agreement in term of penetration depth of an ogival striker into semi-infinite metal target was obtained. It was found by numerical simulation that impact resistance of triple-layered target was higher than double-layered target and monolithic ones. Post-perforation analysis showed the targets were completely perforated and striker's tip was slightly eroded or blunted. Duration of perforation of all targets, damage of their materials were approximately the same, but permanent deformation of additional layers was more in case with a triple-layered targets. This finding can be explained by "pinching effect" of additional layers acting on striker and decelerating it.